Enhancing TFL's Role to Address Potential Failures in Special Allocation Fund Sanitation for MCK Development - Putra, Yocky Syaida Adha; Hadiguna, Rika Ampuh (Peneliti.net, 2023)
This research delves into the crucial factors impacting the success of Special Allocation Fund for Sanitation projects, with a specific focus on the role of Field Facilitators in Ranah Karya Village, Mukomuko Regency. Employing a qualitative descriptive approach and case study methodology, the study underscores the pivotal contributions of Field Facilitators in ensuring the seamless execution of sanitation initiatives. Technical competence, financial management skills, and a comprehensive understanding of the Special Allocation Fund emerge as key factors in averting potential failures. The research advocates for proactive measures, such as providing technical guidance to Field Facilitators before community engagement, to enhance their preparedness. Additionally, effective communication and conflict prevention, facilitated by Field Facilitators as intermediaries between the government, stakeholders, and the community, play a crucial role in project success. The study recommends continuous supervision, focusing on both technical and financial aspects, as a key strategy for smooth project progression. The collaborative efforts between Field Facilitators and stakeholders are emphasized as vital for the ongoing success and sustainability of sanitation projects at the local level. In conclusion, this research offers valuable insights and recommendations to enhance the effectiveness and positive impact of the Special Allocation Fund for Sanitation projects through adept Field Facilitator management